Is it Still Too Early for Collective Redress in Arbitration? – The Boundaries and Opportunities in European Perspectives - Kamilovska, Tatjana Zoroska; Dushkovska, Tatjana Shterjova (Frontiers in Law, 2023)
As has been often stated in judicial practice, collective redress simply reflects the rise of mass production, the diversification of corporate ownership, the advent of the mega-corporation, and the recognition of environmental wrongs. Although the American opt-out class actions are the first thing that comes to mind when one thinks of collective redress, European legislators have been particularly wary regarding the possibility of the US “toxic cocktail" finding their way into European legislations. On the other hand, arbitration, in its basis, is a private way of resolving disputes which is a creation of the parties in the dispute. In its basis there must be consent of the parties to submit the particular dispute to be resolved in arbitration proceedings. Therefore, the possibility to incorporate collective redress mechanism in arbitration proceedings might raise many questions.